2009
DOI: 10.4081/idr.2009.1280
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Dientamoeba fragilis Infections: A Case Report of Two Families from Sydney, Australia

Abstract: We report cases of two unrelated families who both presented with recurrent Dientamoeba fragilis infections. Subsequent antimicrobial therapy resulted in the clearance of D. fragilis and total resolution of gastrointestinal symptoms in both families. This report highlights the potentially recurrent nature of D. fragilis infections and the need for laboratories to routinely test for this organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…Recently, it was also documented that 2 children presented with D. fragilis infection over prolonged periods (Stark et al . 2009). In that study, metronidazole was used initially, but subsequently treatment was done with paramomycin for 10 days to effect clearance of the parasite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was also documented that 2 children presented with D. fragilis infection over prolonged periods (Stark et al . 2009). In that study, metronidazole was used initially, but subsequently treatment was done with paramomycin for 10 days to effect clearance of the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that children are susceptible to infection with D. fragilis and present with clinical symptoms at higher rates than adults (Preiss et al 1991; Ayadi and Bahri, 1999; Crotti et al 2005). Consequently, D. fragilis should be considered in the differential diagnosis of gastrointestinal infections in children (Spencer et al 1979; Keystone et al 1984; Preiss et al 1990; Stark et al 2009) but it is generally ignored as a cause of disease. Clinical symptoms reported include acute and chronic diarrhoea, lower abdominal pain, nausea, flatulence and constipation (Spencer et al 1983; Cuffari et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, several studies found no relationship between Dientamoeba and E. vermicularis (Kean and Malloch, 1966; Walker et al 1985; Oxner et al 1987; Cuffari et al 1998; Menghi et al 2005; Stark et al 2006, 2009 a , 2010 b ). In the study by Kean and Malloch (1966), only 2/100 patients with pure Dientamoeba infections had a history of pinworm infection.…”
Section: The Role Of Helminths In the Transmission Of Dientamoebamentioning
confidence: 96%
“…2004; Stark et al . 2006, 2009, 2010). Despite this, comparatively little information is available about the biology of this organism including genome and proteome studies.…”
Section: Discussionmentioning
confidence: 99%
“…2005 b , Lagace-Wiens et al . 2006, Stark et al 2006, 2007, 2009, 2010), more research with regards to this organism is warranted. The ability to maintain clinical isolates of Dientamoeba in culture for extended periods of time at high cell densities and, the ability to cryogenically preserve viable Dientamoeba trophozoites, would facilitate further study and analysis of this emerging pathogen.…”
Section: Introductionmentioning
confidence: 99%